Current Pharmacological Management of Gastroesophageal Reflux Disease - Yao-Kuang Wang; Wen-Hung Hsu; Sophie S. W. Wang; Chien-Yu Lu; Fu-Chen Kuo; Yu-Chung Su; Sheau-Fang Yang; Chiao-Yun Chen; Deng-Chyang Wu; Chao-Hung Kuo (Gastroenterology Research and Practice)
Gastroesophageal reflux disease (GERD), a common disorder with troublesome symptoms caused by reflux of gastric contents into the esophagus, has adverse impact on quality of life. A variety of medications have been used in GERD treatment, and acid suppression therapy is the mainstay of treatment for GERD. Although proton pump inhibitor is the most potent acid suppressant and provides good efficacy in esophagitis healing and symptom relief, about one-third of patients with GERD still have persistent symptoms with poor response to standard dose PPI. Antacids, alginate, histamine type-2 receptor antagonists, and prokinetic agents are usually used as add-on therapy to PPI in clinical practice. Development of novel therapeutic agents has focused on the underlying mechanisms of GERD, such as transient lower esophageal sphincter relaxation, motility disorder, mucosal protection, and esophageal hypersensitivity. Newer formulations of PPI with faster and longer duration of action and potassium-competitive acid blocker, a newer acid suppressant, have also been investigated in clinical trials. In this review, we summarize the current and developing therapeutic agents for GERD treatment.